P72 TWO SIDES OF THE SAME … PATIENT: CRITICAL LEFT MAIN STEM STENOSIS IN A CANDIDATE FOR TAVI. (18th May 2022) - Varotto, L; Nicoletti, I; Segala, P; Bonanno, C; Angheben, C; Caprioglio, F
Abstract: Best timing for left main stem (LMS) revascularization (staged or combined) is matter of debate in patients with severe aortic stenosis (AS), candidates for transcatheter aortic valve implantation (TAVI). LMS disease represents an additional challenge for 3 reasons: 1) the potential interaction between the coronary stent and the prosthesis due to the anatomic proximity of the LM ostium to the aortic annulus; 2) the risk for hemodynamic compromise during LMS percutaneous coronary intervention (PCI) in the presence of severe AS or TAVI; 3) the optimal treatment strategy for LMS bifurcations. Previous studies showed that outcomes of TAVI plus LMS–PCI were not influenced by an unprotected/protected LMS, the location of the stent or the timing of PCI. Case report. We present the case of an 82–year–old man with severe AS presenting with non–ST–segment elevation myocardial infarction. Coronary angiography revealed a highly complex, calcific LMS lesion. To safeguard the patient, in the event of rapid deterioration of cardiac output and coronary perfusion, a rescue balloon aortic valvuloplasty (BAV) and the Impella device were arranged. PCI was successfully performed by predilatation with Grip and non–compliant balloons, followed by double stenting with Mini–Crush technique. An additional stent in the ostium of the LMS was required without using a circulation support system. Due to the low take–off of the ostium of the LMS, an Edwards Sapien 3 was implanted, protecting the LMS with a guide–catheter and guide–wire. The patient was discharged from hospital on Day 5 post–procedure. Discussion. According to guidelines, decision should be performed case by case, based on the severity/complexity of either AS or LMS disease. The strategy of treating LMS lesions first may limit the risk of potential ischaemic complications during TAVI; its downside is the risk of hemodynamic crash with potential catastrophic evolution in case of PCI complications in severe AS. Mini–crushing can be a good, quick way to treat complex diseases of the LMS bifurcation, less complex to perform in emergency situations. "Bailout BAV" and Impella technology can be helpful bystanders to prevent any complications, being a salvage–strategy in case of advanced status of haemodynamic impairment. These approaches are a very last resort, while appropriate pre–procedural planning is still highly recommended in order to prevent potentially fatal procedural complications in this fragile clinical setting.